Occupation-level income shocks and asset returns: Their covariance and implications for portfolio choice - Steven J. Davis; Paul S. Willen (Federal Reserve Bank of Boston, 2013)
This paper develops and applies a simple graphical approach to portfolio selection that accounts for covariance between asset returns and an investor's labor income. Our graphical approach easily handles income shocks that are partly hedgeable, multiple risky assets, multiple risky assets, many periods, and life cycle considerations. We apply the approach to occupation-level components of individual income innovations estimated from repeated cross sections of the Current Population Survey. We characterize several properties of these innovations, including their covariance with aggregate equity returns, long-term bond returns, and returns on several other assets. Aggregate equity returns are uncorrelated with the occupation-level income innovations, but a portfolio formed on firm size is significantly correlated with income innovations for several occupations, and so are selected industry-level equity portfolios. An application of the theory to the empirical results shows (a) large predicted levels of risky asset holdings compared to observed levels, (b) considerable variation in optimal portfolio allocations over the life cycle, and (c) large departures from the two-fund separation principle.
Keywords: G11; D91; D52; J30; 330; life cycle portfolio choice; risky labor income; graphical approach; occupation-level income shocks